Concentration and dissipation of chlorantraniliprole and thiamethoxam residues in maize straw, maize, and soil. Issue 9 (1st September 2016) - He, Min; Song, Dan; Jia, Hong C.; Zheng, Yongquan
ABSTRACT: To study the dissipation rates and final residual levels of chlorantraniliprole and thiamethoxam in maize straw, maize, and soil, two independent field trials were conducted during the 2014 cropping season in Beijing and Anhui Provinces of China. A 40% wettable powder (20% chlorantraniliprole + 20% thiamethoxam) was sprayed onto maize straw and soil at an application rate of 118 g of active ingredient per hectare (g a.i.ha −1 ). The residual concentrations were determined by ultra-high-performance liquid chromatography–tandem mass spectrometry. The chlorantraniliprole half-lives in maize straw and soil were 9.0–10.8 and 9.5–21.7 days, respectively. The thiamethoxam half-lives in maize straw and soil were 8.4–9.8 and 4.3–11.7 days, respectively. The final residues of chlorantraniliprole and thiamethoxam in maize straw, maize, and soil were measured after the pesticides had been sprayed two and three times with an interval of 7 days using 1 and 1.5 times the recommended rate (72 g a.i. ha −1 and 108 g a.i. ha −1, respectively). Representative maize straw, maize, and soil samples were collected after the last treatment at pre-harvest intervals of 7, 14, and 28 days. The chlorantraniliprole residue was below 0.01 mg kg −1 in maize, between 0.01 and 0.31 mg kg −1 in maize straw, and between 0.03 and 1.91 mg kg −1 in soil. The thiamethoxam residue concentrations in maize, maize straw, and soil were <0.01, <0.01, and 0.01–0.03 mg kg −1, respectively. The final pesticide residues on maize were lower than the maximum residue limit (MRL) of 0.02 mg kg −1 after a 14-day pre-harvest interval. Therefore, a dosage of 72 g a.i. ha −1 was recommended, as it can be considered safe to human beings and animals.